Self-efficacy assessment at the University. A pilot study within the Degree Course in Education and Training Sciences - Alessandra Fermani; Arianna Taddei (Firenze University Press, 2020)
In the process of renewing the assessment models in a socio-constructivist and centred-learner direction, the self-assessment represents a possible declination of the formative assessment in university study paths. It is, in fact, a process that enhances students' critical thinking, to understand both the difficulties and their level of self-efficacy in developing lifelong and lifewide skills, useful as well as in contexts formally assigned to learning, also in real and professional life. The pilot survey, carried out with a group of students from the Degree Course in Education and Training Sciences at the University of Macerata, confirms the importance of self-assessment and focuses attention on the perception of the construct of self-efficacy. The study, in fact, represents the first step of a broader and more complex assessment process, aimed at detecting students' self-efficacy on their socio-cognitive skills pursued by the study profile of socio-pedagogical educator.   Valutare la self-efficacy all'Università. Uno studio pilota nel corso di Scienze dell'Educazione e della Formazione Nel processo di rinnovamento dei modelli di valutazione in direzione socio-costruttivista e learner centred, l'autovalutazione rappresenta una possibile declinazione della valutazione formativa nei percorsi di studio universitari. Si tratta, infatti, di un processo che valorizza il pensiero critico degli studenti, per comprendere sia le difficoltà sia il proprio livello di autoefficacia nello sviluppare competenze di tipo lifelong e lifewide, utili oltre che nei contesti formalmente deputati all'apprendimento, anche nella vita reale e professionale. L'indagine pilota, realizzata con un gruppo di studenti del corso di laurea in Scienze dell'Educazione e della Formazione dell'Università di Macerata, conferma l'importanza dell'autovalutazione e focalizza l'attenzione sulla percezione del costrutto della self-efficacy. Lo studio, infatti, rappresenta il primo passo di un processo di valutazione più ampio e articolato, volto a rilevare la self-efficacy degli studenti sulle proprie capacità di tipo socio-cognitivo perseguite dal profilo di studio di educatore socio-pedagogico.